Garbage Banks For Increasing The Income Of Housewives - Ebenezer Owusu Mensah (CV. AFDIFAL MAJU BERKAH, 2023)
Garbage is an environmental problem and urban society that until now there has been no solution. The limited garbage disposal site (TPA) in Sukoharjo regency, gives this increasingly complex waste problem. The waste bank is one of the alternatives in waste management strategy. The garbage bank is one program that can change the pattern of people's views on waste management. This community service program is partnering with PKK RT 04 RW 03 Wirogunan, Kartasura, where there are around 60 housewives under the PKK. Some problems that exist in partners include. Partners have major problems such as lack of knowledge about the dangers of waste & waste management/sorting and lack of knowledge about waste banks, how to work, and generate income only by sorting and depositing to the waste bank. The method of approach that will be carried out based on an agreement with partners is the socialization of waste and its management, as well as how housewives can earn income from existing waste management. The expected output target is to educate the public to sort waste and deposit waste to the Waste Bank, to create a clean and healthy environment. It is expected that the role of the Village Government in the formation of this garbage bank.